2011
DOI: 10.1038/mt.2011.24
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Microarray-based Analysis of the Host Response to a Nonviral Gene Carrier: A Strategy for Improving the Immune Response

Abstract: The purpose of this study was to investigate the host response to systemically administered lipid nanoparticles (NPs) encapsulating plasmid DNA (pDNA) in the spleen using a DNA microarray. As a model for NPs, we used a multifunctional envelope-type nano device (MEND). Microarray analysis revealed that 1,581 of the differentially expressed genes could be identified by polyethylene glycol (PEG)-unmodified NP using a threefold change relative to the control. As the result of PEGylation, the NP treatment resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…It has been reported that intravenous injection of cationic nanoparticles encapsulating pDNA without PEG modification induced proinflammatory cytokines as well as hepatic toxicity (Hatakeyama H et al, 2011). In contrast, in the case of siRNA systems, IL-6 and IFN-gamma responses were greatly reduced (Table 3).…”
Section: Discussionmentioning
confidence: 84%
“…It has been reported that intravenous injection of cationic nanoparticles encapsulating pDNA without PEG modification induced proinflammatory cytokines as well as hepatic toxicity (Hatakeyama H et al, 2011). In contrast, in the case of siRNA systems, IL-6 and IFN-gamma responses were greatly reduced (Table 3).…”
Section: Discussionmentioning
confidence: 84%
“…However, the response of a host to a systemically administrated non-viral gene vector has not been examined using this approach. We recently conducted a DNA microarray based analysis of the host response to a systemically administered MEND encapsulating pDNA core [24]. In this study, we performed a DNA microarray-based analysis for the systemically administrated PEG-unmodified MEND and PPD/PEG 5K -MEND in the liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…GALA modification diminished the expression of type I IFNs. 35,115) 3.4. pH-Sensitive Cationic Lipids As mentioned above, a cationic characteristic of nucleic acid carriers requires considerable PEG modification to avoid interactions with the biological milieu. Another strategy for overcoming the PEG dilemma is offered by pH-sensitive cationic devices.…”
Section: )mentioning
confidence: 99%